Short implants in the posterior maxilla to avoid sinus augmentation procedure: 5-year results from a retrospective cohort study - Jonas Lorenz; Maximilian Blume; Tadas Korzinskas; Shahram Ghanaati; Robert A. Sader (SpringerOpen, 2019)
Abstract Background Short implants present a promising approach for patients with advanced atrophy to avoid augmentative procedures. However, concerns about increased biological and technical complications due to an unfavorable implant-crown ratio are still present. Purpose The aim of the present retrospective study was to evaluate whether a reduced implant length has any impact on implant success and peri-implant hard and soft tissue health in implants placed in the posterior maxilla to avoid sinus augmentation procedures. Materials and methods Fourteen patients received a total of 30 implants of 7-mm length in the posterior maxilla. Implants with a mean loading period of 5 years (range 2-7 years) were followed up clinically and radiologically, with a focus on the peri-implant soft tissue parameters probing pocket depth (PPD), bleeding on probing (BoP), and the stability of the marginal peri-implant bone level. Results None of the implants were lost, and no technical failures occurred. A mean PPD of 2.5 mm, a mean BoP of 13.3%, and a mean marginal bone loss (MBL) of 0.5 mm indicate healthy peri-implant hard and soft tissue conditions without signs of peri-implantitis. Discussion The present results indicate the suitability of implants of 7-mm length to replace missing teeth in the posterior maxilla. An unfavorable implant-crown ratio or reduced bone-implant contact length seems to have no negative influence on midterm implant success or on peri-implant hard and soft tissue health.